Optimal Location of the Active Thermal Insulation Layer in the Building Envelope - Barbara Król; Krzysztof Kupiec (Thermo, 2023)
One of the modern methods of protecting against building heat losses is active thermal insulation (ATI). In winter conditions, ATI works by supplying heat into the envelope, which increases the temperature in the ATI layer. A low-temperature renewable energy medium feeds the active insulation layer directly, e.g., through solar or geothermal energy. A model for heat transfer through the building envelope with an ATI layer was developed. The numerical simulations verified the simplifying assumptions in the model. A relationship was derived to determine the optimal location of the ATI layer in the envelope. The objective function of the summed costs of the thermal energy supplied to the internal space and the envelope was assumed. We took into account the fact that the unit price of energy supplied to the ATI layer is lower than the price of the energy supplied to the internal space. Based on the results of the measurements carried out in a building facility with the ATI layer installed, the actual savings effects due to the ATI layer were compared to the calculated values.